2015
DOI: 10.3109/03014460.2015.1031825
|View full text |Cite
|
Sign up to set email alerts
|

The epiphyseal scar: changing perceptions in relation to skeletal age estimation

Abstract: Background: It is imperative that all methods applied in skeletal age estimation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The value of the physeal scar for age estimation has always been doubted, in studies on the clavicle, 4,6 as well as in studies on other long bones. [19][20][21] Correspondingly, the current findings suggested no loss in age estimation performance by merging stages 4 and 5. However, the disappearance of the physeal scar might be important in individuals who are older than the current sample.…”
Section: Discussionsupporting
confidence: 66%
“…The value of the physeal scar for age estimation has always been doubted, in studies on the clavicle, 4,6 as well as in studies on other long bones. [19][20][21] Correspondingly, the current findings suggested no loss in age estimation performance by merging stages 4 and 5. However, the disappearance of the physeal scar might be important in individuals who are older than the current sample.…”
Section: Discussionsupporting
confidence: 66%
“…Radiological studies have also shown visible remnants of the growth plate (physeal scar) on radiographs both in the knee 25 and upper extremity. 26 , 27 Faisant et al. 25 showed a physeal scar in at least one of the bones of the knee joint in 96% of females and 98% of the males in a population aged between 15 and 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although sometimes utilized as a synonym for epiphyseal scar (Albert & Maples, ; Cardoso, ), we use the term epiphyseal line to refer to the “line” marking the junction between epiphyses and metaphyses on the surface of a dry bone. Unlike what was observed for the epiphyseal line, the epiphyseal scar (observed radiographically) on the tibia and radius does not seem to be related to age (Davies et al, , , ). In addition, Faisant et al (), who analyzed the knee joint, found no indication that the longevity of the epiphyseal scar might be a possible indicator of recent fusion, therefore lacking a correlation with biological age.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies conducted by radiography have stressed that, once the epiphyseal‐diaphyseal fusion is completed, the persistence of an epiphyseal scar may still be visible in some adults (Baumann et al, ; Cameriere, Cingolani, Giuliodori, De Luca, & Ferrante, ; Cope, ; Flecker, ; Krogman & İşcan, ; O'Connor, Coyle, Spence, & Last, ; Schmeling et al, ; Schulz et al, ; Schulz, Mühler, Reisinger, Schmidt & Schmeling, ; Todd, ; Walker & Lovejoy, ). In seeking a possible correlation between this trait and age, a persistence of the scar has been observed until the fifth decade of life, but with no significant correlation, suggesting that its occurrence might depend on other factors, such as living conditions and environmental influences on its distribution (Davies, Hackman, & Black, , , ; Faisant et al, ). In dry bone examinations, it has been observed that the epiphyseal line persists into adulthood (Albert & Maples, ; MacLaughlin, ; Stevenson, ).…”
Section: Introductionmentioning
confidence: 99%